Consumers' valuation on food safety attributes - Nurul Nadia Ramli; Khalid Joya; Mad Nasir Shamsudin; Nitty Hirawaty Kamarulzaman (Penerbit Universiti Kebangsaan Malaysia, 2023)
The objective of this study is to determine the consumers’ valuation or willingness to pay (WTP) for the safety attributes of cabbage. The survey was conducted in Klang Valley, Malaysia from September to November 2019 involving 505 respondents. This study employed the discrete choice experiment (DCE) and found that the important safety attributes of cabbage demanded by consumers were appearance, followed by the type of production system, cabbage with myGAP certification and the type of market (point of purchase of cabbage). The sociodemographic variables such as age, income and education level also can influence the WTP for the safety attributes of cabbage. The findings suggested that the older consumers and the consumers with higher income and education were willing to pay more for safety attributes of cabbage. Thus, these findings can be utilized by the producers and marketer to design appropriate production and marketing strategies to meet the demand from these group of consumers and consequently can be translated into business opportunities.